Frontomaxillary Facial Angle Measurement in Screening for Trisomy 18 at 11 + 0 to 13 + 6 Weeks of Pregnancy: A Double-Centre Study. (1st October 2013) - Czuba, Bartosz; Cnota, Wojciech; Wloch, Agata; Wegrzyn, Piotr; Sodowski, Krzysztof; Wielgos, Miroslaw; Borowski, Dariusz
Abstract : Objective . The aim of this study was to evaluate the effectiveness of prenatal screening for trisomy 18 with the use of the frontomaxillary facial angle (FMF angle) measurement. Material and Methods . The study involved 1751 singleton pregnancies at 11–13 + 6 weeks, examined between 2007 and 2011. Serum PAPP-A and free beta-hCG levels were assessed, and crown-rump length, nuchal translucency, and FMF angle were measured in all patients. 1350 fetuses with known follow-up were included in the final analysis. Results . Highly significant (P < 0.01 ) negative correlation between the CRL and the FMF angle was found. There were 30 fetuses with trisomy 18. FMF angle was highly significantly larger (P < 0.0001 ) in fetuses with trisomy 18 as compared to chromosomally normal fetuses. Two models of first trimester screening were compared: Model 1 based on maternal age, NT, and first trimester biochemistry test (DR 80–85% and FPR 0.3–0.6%), and Model 2 = Model 1 + FMF angle measurement (DR 87.3–93.3% and FPR 0.8–1.3%). Conclusions . The use of FMF angle measurement increases the effectiveness of the screening for trisomy 18. Introduction of the FMF angle as an independent marker for fetal trisomy 18 risk requires further prospective research in large populations.